Penerapan Model Pembelajaran Team Games Tournament (TGT) untuk Meningkatkan Hasil Belajar Siswa Kelas XI pada Materi Laju Reaksi di SMAN 3 Padang Panjang - Pratiwi, Fitra Adinda; Lufri, Lufri; Yerimadesi, Yerimadesi; Asnizar, Asnizar (YASIN, 2025)
The limited number of studies on the implementation of the cooperative learning model Team Games Tournament (TGT) in the context of chemistry education serves as the background for this research, particularly in addressing the issues of low student engagement and learning outcomes, which affect the overall effectiveness of classroom instruction. This study aims to improve the learning outcomes and engagement of Grade XI students on the topic of reaction rate through the application of the TGT cooperative learning model. The method used was Classroom Action Research (CAR), conducted in two cycles involving 35 students from Class XI Chemistry 4 at SMAN 3 Padang Panjang, selected through purposive sampling. Data were collected through observations of learning activities during instruction and learning outcome tests administered at the end of each cycle. The data were analyzed using descriptive qualitative and quantitative methods. The findings show a significant improvement in student learning outcomes, with classical completeness increasing from 69% in the first cycle to 86% in the second, and student engagement rising from 54% to 77%. These results indicate that the TGT model is effective in enhancing both student achievement and active participation, aligning with cooperative learning theory, which emphasizes the role of social interaction and constructive competition in fostering motivation and conceptual understanding. This study contributes to the development of enjoyable and meaningful chemistry teaching strategies and recommends TGT as a promising alternative for increasing student involvement and achievement, while also encouraging further research on this model across different topics and educational levels.